2015
DOI: 10.1002/pits.21838
|View full text |Cite
|
Sign up to set email alerts
|

Principal Attitudes Regarding Zero Tolerance and Racial Disparities in School Suspensions

Abstract: Zero tolerance school discipline practices have been associated with a national increase in suspensions, a practice that has had a disproportionate negative impact on Black students. The present study investigated an association between principal attitudes toward zero tolerance and suspension rates for White and Black students in 306 Virginia high schools. Black suspension rates were more than double White suspension rates. Regression analyses controlling for student poverty and school enrollment showed that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 24 publications
(28 reference statements)
1
22
0
Order By: Relevance
“…This phenomenon is not unique to Indigenous people in Australia; studies show that many of Canada's First Nations, Métis and Inuit peoples, who also experienced European subjugation and control during invasion and colonisation, now suffer from intergenerational trauma, deep social and economic disadvantage and high rates of incarceration (Jackson Pulver et al, 2010). Exclusion from education has also been identified as a contributing factor to the early incarceration of young people (Heilbrun et al, 2015; Raible & Irizarry, 2010; Welch & Payne, 2010).…”
Section: The ‘School To Prison Pipeline’mentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon is not unique to Indigenous people in Australia; studies show that many of Canada's First Nations, Métis and Inuit peoples, who also experienced European subjugation and control during invasion and colonisation, now suffer from intergenerational trauma, deep social and economic disadvantage and high rates of incarceration (Jackson Pulver et al, 2010). Exclusion from education has also been identified as a contributing factor to the early incarceration of young people (Heilbrun et al, 2015; Raible & Irizarry, 2010; Welch & Payne, 2010).…”
Section: The ‘School To Prison Pipeline’mentioning
confidence: 99%
“…Turning our attention briefly to international research, Heilbrun et al, (2015) found that children in minority groups in the United States were most at risk of the ‘zero tolerance’ policy reforms. Their research indicates a host of negative consequences resulting from the suspension and exclusion of young people from schools, including higher levels of contact with police and higher levels of incarceration in juvenile justice facilities (Heilbrun et al, 2015).…”
Section: Incarcerationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, African American youth have disproportionately received in‐school detentions and suspensions in comparison to white counterparts. Among a sample of 306 Virginia high school students, Heilbrun, Cornell, and Lovegrove (2015) found that African American students experienced almost twice the amount of suspension compared with Caucasian students. African American students were also found to be more likely to experience suspensions due to disruptiveness that interfered with the learning environment while Caucasian students were more likely to be suspended for more serious behaviors, including the use of alcohol or illicit substances (Heilbrun et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, study findings show that parentperceptions of self-defense go beyond physical fighting skills and include items such as (a) the ability to remain calm during conflict, (b) building strong verbal skills, (c) understanding how to escalate to appropriate authority figures, and (d) using restraint when physical force is required. Social trends such as zero tolerance require specific skills during conflict management (Heilbrun et al, 2015;Ward, 2014). Martial arts firms should create marketing messages that emphasize self-defense benefits and the confidence and soft skills mentioned above toenable students to defend themselves and de-escalate conflict appropriately without violence in zero-tolerance environments.…”
Section: Recommendations For Practicementioning
confidence: 99%